Innovative local prestressing system for concrete crossties using shape memory alloys. (15th November 2021) - Sung, Minsoo; Andrawes, Bassem
Highlights: A new prestressing system using SMAs is proposed and experimentally validated. The new system can apply prestressing selectively at a target region. Shear prestress is applied effectively with the use of non-straight reinforcement. Greater cracking resistance of the proposed system than the conventional system. Abstract: This paper focuses on introducing and investigating a new prestressing system for railroad concrete crossties using shape memory alloys (SMAs). Concrete crossties are typically prestressed with straight high strength steel wires throughout the entire length, which could lead to splitting cracks at end regions and excessive compressive stress concentration at compressive zones. A new prestressing system with adjustable wire configuration allows prestressing force to be applied selectively at target regions in the crosstie. The proposed prestressing system can help prevent end-splitting cracks, adjust prestressing force depending on the demands at different sections, and adjust the reinforcement configuration along the length. In the proposed system, pre-strained SMA wires are placed in the forms prior to casting the concrete at the locations where prestressing is needed. After the concrete is set, the prestressing force can be applied at any time by activating the SMA wires using electrical resistivity heating. In this work, both experimental and numerical studies using SMAs (NiTiNb) are presented for proof of concept. Three small-scale concrete crosstie specimens with different SMA wire configurations are tested. Comparison between the SMA prestressed concrete crosstie model and steel prestressed model is performed using finite element analysis considering prestress losses. The results indicate that the new prestressing system can effectively apply prestress at target regions as designed.